MANAJEMEN PENGEMBANGAN WAKAF PRODUKTIF ERA DIGITAL DI LEMBAGA WAKAF BANI UMAR - Syaifullah, Hamli Syaifullah; Idrus, Ali (Al-Khidmat : Jurnal Ilmiah Pengabdian Kepada masyarakat, 2019)
The Community Service Program (PKM) for internal lecturers tries to collaborate with The Bani Umar Waqf Institute, an institution that is concerned in collecting and developing waqf assets to be more productive. The method used is case studi, with direct involvement with the Bani Umar Waqf Institute for approximately 6 months. From the initial review of the author at The Bani Umar Waqf Institute, found two crucial problems that exist within the institution, namely regarding the lack of human resources and marketing channels. Then, the authors propose two concepts to answer these crucial problems, namely the concept of Human Resource Management based on volunteers, and create digital-based marketing channels.Â